Frequency of Hyponatremia in Children With Bronchiolitis - Amir Rashid, Muhammad Waqas Anwar, Sammer Saeed, Khaver Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bronchiolitis is predominant among infants and mostly caused by respiratory syncytial virus (RSV). Respiratory illnesses are related to elevated anti-diuretic hormone which in turn leads to hyponatremia (<135 mmol/L) Aim: To find hyponatremia frequency in bronchiolitis children. Methods: From December 8, 2017 to June 8, 2018, researchers from the pediatrics department of Lahore General Hospital/Post Graduate Medical Institution conducted a cross-sectional study. All 246 cases meeting inclusion criteria were taken from department of Pediatrics, Lahore General Hospital, Lahore. After taking informed consent all the basic information like age, sex and contact detail was taken. Blood sample sent to hospital laboratory to evaluate serum sodium levels to find hyponatremia as per operational definition. Data input and analysis were carried out using SPSS version 20. Results: With ages ranging from 2 to 24 months, the mean age was 13.29 6.35 months. There were 124(50.4%) male and 122(49.6%) female cases and male to female ratio was the same. The mean Na level in all cases was 130.86 ± 6.61 mEq/L with minimum and maximum value as 115 and 145 mEq/L respectively. A total of 192(78%) cases had hyponatermia while other 54(22%) cases had normal Na+ level. Conclusion: According to findings of this study it was concluded that frequency of hyponatermia was too high in children with Bronchiolitis i.e. 78%. So when a child present with Bronchiolitis he must be evaluated for Na+ level, and if it is low then sodium levels should also be corrected along with the treatment of bronchiolitis. Keywords: Bronchiolitis, Electrolyte imbalance, Hyponatermia, ICU, treatment prognosis.